Design and Build Employee Payroll Applications at CV. Surya Jaya Motor - Nur Afifah Handayani; Arifin Puji Widodo; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
CV. Surya Jaya Motor is a service company that was founded in 1987. CV. Surya Jaya Motor is located on Jl. Raya Berbek 19 Waru sub-district, Sidoarjo regency. In carrying out the payroll process for employees at this company it is not integrated with the system, data and salary components are processed manually in a short time, in searching for information there is a risk of loss or damage to data, the process of raising salaries requires data on the initial work period of employees that must be searched regularly. one by one to determine the length of work. Based on the problems that occur, the solution provided is in the form of a payroll application that can calculate attendance, calculate employee salaries according to the provisions of the company, record employee overtime, manage employee salary increases to facilitate related parties regarding salary payments to each employee. The system is made according to the demands and needs of the company. The method used is SDLC (Software Development Life Cycle) as a stage in making employee payroll applications.The system created can produce employee salary information based on the existing salary components in the company, attendance, employee overtime and employee salary increases that can help companies pay employee salaries.